Development of Video Tutorial Practicum of Human Blood Circulation to Support Biological Learning in The Covid-19 Pandemic Time - sari, Intan mei susan anggoro; Risnani, Listika Yusi (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2021)
Developing Practicum Tutorial Video For High School Students On The Human Blood Circulation In The Eleventh Graders Of Science Class To Support Biology Learning In The Covid-19 Pandemic Time. The government requires educators to use technology-based e-learning such as a practicum tutorial video for students. The purpose of this study was to develop a tutorial video for a practicum on human blood circulation material for high school students in the eleventh grade of IPA class in order to support Biology learning during the Covid-19 pandemic. This was a research and development using the ADDIE model having five stages, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The instrument of the study used a questionnaire and test. The questionnaire was used as the measurement of learning media in the form of a tutorial video, and the test was used as a cognitive (knowledge) measurement. Based on the results, the video tutorial practicum had a good score of 3 tested by media and material experts, a score of 3.66 in the very good category assessed by the teachers, an average score of 2.96 with the results in the good category assessed by the students. Thus, the developed practicum tutorial video is feasible as the learning medium on human blood circulation material for practicum activity during the Covid-19 pandemic